A Patient With Progressive Cognitive Decline and Periodic Abnormal Waves in EEG: PLEDs of Neurosyphilis or PSDs of Creutzfeldt–Jakob Disease?. (July 2014) - Lv, Yudan; Chu, Fengna; Meng, Hongmei; Wang, Zan; Cui, Li
We report one Chinese patient with neurosyphilis exhibiting periodic lateralized epileptiform discharges (PLEDs) in the electroencephalogram (EEG). The patient (male, 59 years old) manifested with progressive cognitive decline and abnormal behavior. After several days, he gradually lost contact with others, and fell into a coma. EEG revealed periodic abnormal waves, predominantly located in the right anterior frontal region. The serum and cerebrospinal fluid Venereal Disease Research Laboratory test and Treponema pallidum hemagglutination assay were positive. Magnetic resonance imaging (MRI) of brain showed focal atrophy in the right frontal and temporal region. Diffusion-weighted MRI showed "lace sign" in cortex, which could be seen as an early and special feature in Creutzfeldt–Jakob disease (CJD). To differentiate "PLEDs of neurosyphilis on EEG" from "periodic synchronous discharges (PSD) of CJD on EEG, " we treated this patient with diazepam 20 mg intravenously. After 10 minutes, periodic abnormal waves on EEG disappeared, with improved mental status, which confirmed the diagnosis of PLEDs of neurosyphilis. Then, after the treatment with penicillin, the patient improved and returned to work.